SEMICONDUCTORS OF CRYSTALLIN ALLOYS IN SUPERLATTICES - Luciano Nascimento Nascimento; Lourdes Cristina Lucena Agostinho Jamshidi; Celmy Maria B. de Menezes Barbosa; Reza Jamshidi Rodbari (Revista Tecnológica, 2015)
This work analyzes, from the effects related to the processes of transportation of carrier and the changes in the electronic structure of semiconductors materials due to the presence of defects and disorders in the crystalline net. These defects are located in specific areas of the material and either interact or remain inert. In general, they are described by local wave functions. The study of superlattices of semiconductor crystal considers important parameters such as disorder effects in crystals and the alternate periodic growth of the layer of two semiconductors with different gaps and minigaps energies. The quantum mechanical calculations are applied for determining the physical properties of the semiconductors crystals. This study encompasses the effects of defects and the crystalline disorders evaluation by quantum mechanics. Further, it is discuss the presence of defects in the periodic, quasiperiodic and disordered arrangements. The theoretical approach use to understand the mechanism and the results of experimental techniques in which are characterized the current and optic transportation of a semiconductor crystal.